Determining the molecular basis for the pH-dependent interaction between 2′-deoxynucleotides and 9H-pyrido[3,4-b]indole in its ground and electronic excited states - Gonzalez, M. Micaela (2014)
Interaction between norharmane and three different 2′-deoxynucleotides (dNMP) (2′-deoxyguanosine 5′-monophosphate (dGMP), 2′-deoxyadenosine 5′-monophosphate (dAMP) and 2′-deoxycytidine 5′-monophosphate (dCMP)), in aqueous solution, was studied in the ground state by means of UV-vis and ¹H-NMR spectroscopy and in the first electronic excited state using steady-state and time-resolved fluorescence spectroscopy. In all cases, the norharmane–dNMP interaction dependence on the pH was examined. Possible mechanisms for the interaction of both ground and electronic excited states of norharmane with nucleotides are discussed. Spectroscopic, molecular modeling and chemometric analysis were performed to further characterize the chemical structure of the complexes formed and to get additional information concerning the interaction between dNMPs and norharmane.